Friction stir butt welding of Al-Cu bilayer laminated composites: analysis of force, torque, and temperature. Issue 1 (January 2017) - Beygi, R.; Kazeminezhad, M.; Mehrizi, M.; B, G.; Loureiro, A.
Abstract The effect of the layer in contact with tool (Al or Cu) and the depth of plunge on friction stir butt welding of Al-Cu bilayer laminated composites produced by cold roll welding were studied. The measurement of weld cross sections and variations of the axial load and torque during welding process showed that material flow is influenced by the material which is in contact with the shoulder. Being Al layer in contact with the shoulder led to higher force and torque during welding, and a defect-free weld could be obtained in this manner. By welding from Cu side, a higher plunge depth was needed to develop enough force and torque and thereby a defect-free weld. The amount of material swept by the shoulder and flow stress of the material in contact with shoulder have determined the force and torque and also temperature during welding.